2019
DOI: 10.1186/s13019-019-0919-6
|View full text |Cite
|
Sign up to set email alerts
|

Giant cavernous hemangioma of the eleventh rib

Abstract: Background Cavernous hemangioma of the rib is extremely rare benign vascular tumor. It is difficult to diagnose in time because both invasive and noninvasive examinations usually fail to distinguish it from other tumors of the rib and other bones. Case presentation We described an asymptomatic 44-year-old woman with cavernous hemangioma of the rib that was incidentally discovered in the bathing. The tumor was completely resected by minithoracotomy through posterolateral… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0
1

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 7 publications
0
4
0
1
Order By: Relevance
“…Les hémangiomes caverneux sont les plus courants et représentent jusqu'à 50 % de tous les hémangiomes. Ils consistent en des vaisseaux dilatés bordés par une seule couche de cellules endothéliales entourées www.odermatol.com d'une couche stromale fibreuse [3]. La plupart des hémangiomes caverneux sont de localisation profonde touchant le système nerveux,l'orbite, l'os et le muscle.…”
Section: Discussionunclassified
“…Les hémangiomes caverneux sont les plus courants et représentent jusqu'à 50 % de tous les hémangiomes. Ils consistent en des vaisseaux dilatés bordés par une seule couche de cellules endothéliales entourées www.odermatol.com d'une couche stromale fibreuse [3]. La plupart des hémangiomes caverneux sont de localisation profonde touchant le système nerveux,l'orbite, l'os et le muscle.…”
Section: Discussionunclassified
“…Such cases require combined rib resection or chest wall reconstruction. 2 In addition, Shimizu et al 3 reported an intercostal cavernous hemangioma that grew from 1.8 to 6.0 cm during a 3-year follow-up period. In contrast, Hashimoto et al 4 reported no recurrence of a small intercostal cavernous hemangioma of 1.2 cm after tumor extirpation using video-assisted thoracic surgery (VATS).…”
Section: Discussionmentioning
confidence: 99%
“…Several surgical cases of large intercostal cavernous hemangiomas measuring >4 cm have been reported since the year 2000. Such cases require combined rib resection or chest wall reconstruction 2 . In addition, Shimizu et al 3 reported an intercostal cavernous hemangioma that grew from 1.8 to 6.0 cm during a 3‐year follow‐up period.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of hemangiomas of bone involve vertebral bodies, followed by the craniofacial skeleton and long bones. Hemangioma of the rib is rare, with only 33 cases of rib hemangiomas, including our two cases, described in the English literature to date [ 2 9 ]. In the literature and our cases, the median patient age was 50 years (range, 11–76 years).…”
Section: Discussionmentioning
confidence: 99%
“…Curettage for vascular tumors also has the risk of large bleeding events during the surgical procedure. Therefore, en bloc excision is typically performed for rib hemangioma [2][3][4][5][6][7][8][9]. On the basis of previous report [15], en bloc excision with at least a 2 mm margin is advisable for obtaining optimal oncological outcomes in patients without biopsy…”
Section: Discussionmentioning
confidence: 99%